THE ROLE OF POLITICAL PARTIES IN FOSTERING CONSTITUENT AWARENESS IN PARTY CADRES (CASE STUDY OF DPD PARTAI KEADILAN SEJAHTERA OF SERANG CITY) (STUDI KASUS DPD PARTAI KEADILAN SEJAHTERA KOTA SERANG) - Miftah Hulhilman; Damanhuri; Ronni Juwandi (Institut Pendidikan Indonesia, 2022)
This study aims to find out the role of the Serang City Partai Keadilan Sejahtera in growing constituent awareness in its party cadres, knowing the understanding of the Serang City Partai Keadilan Sejahtera cadres regarding constitutional awareness and knowing the role of the Serang City Partai Keadilan Sejahtera to prevent its cadres from committing corrupt acts. This research uses a qualitative approach with a case study method. The results found are that the Serang City PKS has indeed made efforts to instill constituent awareness in its cadres through the party's regeneration system, both through education, training, and coaching. Then the cadres of the Serang City PKS already have a fairly good understanding of constituent awareness. This is based on that the cadres of the Serang City PKS already have an understanding of the importance of having constituent awareness, to be good citizens and also to become party cadres who understand the nature and purpose of partying is to contribute to building the country. Then the Serang City PKS has a way to overcome corruption cases, both ways to prevent and overcome. The way for the Serang City PKS to prevent its cadres from corruption through the cadreization system is carried out strictly and sustainably. Be it in coaching, education, or training activities and how to overcome it through actions taken by the Regional Ethics Council.